Tindak Tutur Ilokusi dalam Podcast Jk-W dan Nd-M dalam Kanal Youtube serta Manfaatnya sebagai Bahan Ajar Pragmatik di Perguruan Tinggi - Sari, Novita; Budiyono, Herman; Purba, Andiopenta (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
In the era of 4.0, podcasts have become a new and interesting medium of information. For this reason, this study aims to describe (1) the types of illocutionary discourse acts, (2) the types of illocutionary discourse acts in Podcasts on the Youtube channel, and (3) their advantages as material for pragmatic shows in universities. The research method uses descriptive qualitative methods with the help of pragmatic analysis. The source of information in this study is the discourse expressed by speakers and presenters on podcasts on the Jk-W and Nd-M Podcast Youtube channels. Information sorting method in this research is for nothing listening procedure (SBLC) and note-taking strategy. The examination instrument used in this research is the scientist himself (human instrument). Given the information check, three ends can be drawn. First, the types of illocutionary discourse acts found are assertive, mandated, commissive, and expressive and announcements. Second, the elements of illocutionary discourse acts found are serious, beautiful, fun, and problematic. Third, the thing that arises because of this exam is through teaching materials that can be used as pragmatic learning in higher education.